Conceptual Art - Meyer, Ursula (New York : E.P. Dutton & Co, Inc., 1972)
Acconci ; Atkinson ; Bainbridge ; Baldessari ; Barry ; Barthelme ; Battcock ; Becher, B. & H. ; Bochner ; Buren ; Burgin ; Burgy ; Burn / Ramsen ; Castoro ; Cutforth ; dibbets ; Fernbach-Flarsheim ; Graham ; Haacke ; Huebler ; Kaltenbach ; Kawara ; Kirili ; Kosuth ; Kozlov ; Lewitt ; Merz ; Morris ; Nauman ; N.E. Thing Co. (Iain Baxter) ; Oppenheim ; Perreault ; Piper ; Ramsden ; Ruscha ; Venet ; Weiner ; Wilson
Engels
boek